Pengaruh Literasi Keuangan dan Teman Sebaya Terhadap Perilaku Keuangan dengan Gaya Hidup Sebagai Variabel Mediasi Pada Mahasiswa Institut Bisnis dan Ekonomi Indonesia - Ecci Resamala Sari; Yusron Toto; Yuniarti Yuniarti; Sukma Febrianti (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2025)
This research aims to analyze and determine the influence of financial literacy and peers on financial behavior with lifestyle as a mediating variable (Study of students at the Indonesian Institute of Business and Economics). The population of this study was 821 IBE Indonesia students class 2021- 2024, the sampling technique used purposive sampling and the sample formula was Taro Yamane with an error rate of 5%, a sample of 268 respondents was obtained. The data collection technique uses a questionnaire from Google Form and the data analysis tool uses Smart PLS 4.0. The data analysis technique uses PLS-SEM. Based on the results of this research, it can be concluded that financial literacy has a positive influence on financial behavior. Apart from that, the existence of peer variables also has a significant positive impact on financial behavior. Financial literacy and peers also contribute positively and significantly to lifestyle. Finally, lifestyle plays a role in mediating the relationship between financial literacy and financial behavior, as well as between peers and financial behavior.